IMPLEMENTASI GERAKAN LITERASI SEKOLAH DALAM MENINGKATKAN MINAT BACA SISWA KELAS IX SMPN 70 BENGKULU UTARA - Vera Budi Asih (FAJAR Jurnal Pendidikan Islam, 2024)
In order to enhance reading interest, SMP Negeri 70 Bengkulu has implemented a Literacy Movement for all students. This includes the establishment of reading huts and classroom reading corners, or Library Corners, supported by a well-equipped library. The initiative encourages students to read not only textbooks but also non-textbook materials. The focus of this research is: 1) How is the implementation of the school's literacy movement at the habituation stage? 2) How is the implementation of the school's literacy movement at the development stage? 3) How is the implementation of the school's literacy movement at the learning stage in improving students' reading interest at SMP Negeri 70 Bengkulu? The research uses a qualitative approach and employs a phenomenological study method. Data collection methods include observation, interviews, and documentation, while data analysis uses an interactive model, consisting of data collection, data condensation, data display, conclusion drawing, and verification. The results of this study are: First, the habituation stage involves a daily 15-minute reading session, either aloud or silently, conducted at the beginning, middle, or end of lessons. The titles and authors of the books read by the students are recorded in a daily journal. Second, the development stage involves a 15-minute reading session before lessons begin. Students engage in responding to enrichment books during literacy hours or in the library, classroom reading corners, or other relevant lesson periods. The school offers a varied collection of enrichment books. Third, the learning stage, which has already been implemented at SMP Negeri 70 Bengkulu, incorporates the use of enrichment books in all subjects. Reading strategies are employed to improve students' comprehension of texts across all subjects. Students respond to readings through activities such as oral presentations, written work, art, and other forms of expression in line with their literacy skills.